2023
DOI: 10.3233/thc-220533
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a supervised online group exercise program on symptoms associated with patellofemoral pain syndrome in women

Abstract: BACKGROUND: Patellofemoral pain syndrome (PFPS) is one of the musculoskeletal system pathologies frequently encountered especially in women. OBJECTIVE: The aim of the current study was to compare the efficacy of an online exercise program with a home exercise program including the same exercises, and a control group planned for females with PFPS. METHODS: The study included 60 females with PFPS aged 33.17 ± 6.84. Participants were randomly divided into 3 groups. One of the groups was given a 6-week home progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In a prospective clinical trial, Albornoz-Cabello et al reported that a tele-prescription program through a pamphlet containing the description of exercises and phone call control by a physical therapist could be effective in reducing pain and disability in PwPFPS during the COVID-19 pandemic [ 33 ]. In a study by Arslan et al, telerehabilitation through online supervised exercise programs decreased pain and kinesiophobia and increased the quality of life in female PwPFPS [ 34 ]. This study compared the effect of an online supervised exercise program and a home exercise program with a control group that did not receive any intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective clinical trial, Albornoz-Cabello et al reported that a tele-prescription program through a pamphlet containing the description of exercises and phone call control by a physical therapist could be effective in reducing pain and disability in PwPFPS during the COVID-19 pandemic [ 33 ]. In a study by Arslan et al, telerehabilitation through online supervised exercise programs decreased pain and kinesiophobia and increased the quality of life in female PwPFPS [ 34 ]. This study compared the effect of an online supervised exercise program and a home exercise program with a control group that did not receive any intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Daveri handouts in training programs and concluded that supervised training was the most effective method [13]. Arslan et al conducted online training for women with patellofemoral pain syndrome and reported that the group provided with direct instructions experienced less pain and fear during the activity [14]. These findings suggest that online personal training can be an alternative to traditional face-to-face training and that the provision of direct instructions under the supervision of a trainer is more effective than on-demand training.…”
Section: Introductionmentioning
confidence: 99%